DYNAMIC TEACHING RATIO PEDAGOGIC MODEL - Jiaying, Chen; Kheng, Wee Keat; Kiong, Soh Guan (Journal of Technical Education and Training, 2010)
This paper outlines an innovative pedagogic model, Dynamic Teaching Ratio (DTR) Pedagogic Model, for learning design and teaching strategy aimed at the postsecondary technical education. The model draws on the theory of differential learning, which is widely recognized as an important tool for engaging students and addressing the individual needs of all students. The DTR model caters to the different abilities, interest or learning needs of students and provides different learning approaches based on a student’s learning ability. The model aims to improve students’ academic performance through increasing the lecturer-to-student ratio in the classroom setting. An experimental case study on the model was conducted and the outcome was favourable. Hence, a large-scale implementation was carried out upon the successful trial run. The paper discusses the methodology of the model and its application through the case study and the large-scale implementation.